PENERAPAN MODEL PICTURE TO PICTURE UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEXS DESKRIPSI - Ibrahim, Mujizat Maulana (2015)
This study aims to improve the writing skills of students through the text description of the application of the model picture to picture. This model is one model of learning that uses images as a medium in the learning process. The displayed image is the image of the dance area. Through this image of students directed to have the skills to write a text description. The method used is a Class Action Research (PTK). Research subjects are students of class VII A SMPN I Cipongkor, West Bandung Regency academic year 2014/2015. Procedures for implementing the action is divided into two cycles with each cycle of four components, namely planning, action, observation, and reflection. Data collection techniques used are observation, field notes, questionnaires, interviews, written tests, and photo documentation. The research instruments used include observation sheet, field notes, questionnaires, evaluation sheets description writing skills, interview and photo recording tool. Data were analyzed with descriptive analysis techniques supported by qualitative and quantitative data. Criteria for success of the action is divided into two, namely the processes and products. The success of the process is measured by the increase in the learning process into a better direction. The success of the product is measured based on student achievement indicators and a better value. The results showed that the application of the Model Picture to Picture can increase the skill of writing a text description of the class VII A SMPN I Cipongkor West Bandung regency. Improved looks at the process and product. Improved process looks at the activity of students in learning. This increase is evident from the condition of the students are more focused, more enthusiastic, more independent, more active, and happy in the learning activities. Improving the quality of the process have a positive impact on improving product quality. This is evident in the results of the test write descriptions of sikluss I to cycle II increased. The average value of the class in the first cycle, which amounted to 63 and the second cycle of 83. Writing text description using the model picture to picture facilitate and engage students in the discovery and casting ideas. It can be concluded that the model picture to picture by using media images of local dance is one technique that can improve the writing skills of students in the description text SMPN 1 Cipongkor. Penelitian ini bertujuan untuk meningkatkan keterampilan menulis teks deskripsi siswa melalui penerapan model picture to picture. Modelinimerupakan salah satu model pembelajaran yang menggunakan gambar sebagai media dalam proses pembelajaran. Gambar yang ditampilkan adalah gambar tarian daerah.Melalui gambar inisiswa diarahkan untuk memiliki ketrampilan menulis teks deskripsi. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK).Subjek penelitian yaitu siswa kelas VIIA SMPN I Cipongkor, Kabupaten Bandung Barat tahun ajaran 2014/2015.Prosedur pelaksanaan tindakan terbagi dalam dua siklus dengan empat komponen pada tiap siklusnya, yaitu perencanaan, pelaksanaan tindakan, pengamatan, dan refleksi.Teknik pengumpulan data yang digunakan adalah pengamatan, catatan lapangan, angket, wawancara, tes tertulis, dan dokumentasi foto.Instrumen penelitian yang digunakan meliputi lembar observasi, catatan lapangan, angket, lembar penilaian keterampilan menulis deskripsi, pedoman wawancara, dan alat rekaman foto.Data dianalisis dengan teknik analisis deskriptif kualitatif dan didukung dengan data kuantitatif. Kriteria keberhasilan tindakan dibagi menjadi dua, yaitu proses dan produk. Keberhasilan proses diukur berdasarkan peningkatan proses pembelajaran ke arah yang lebih baik. Keberhasilan produk diukur berdasarkan ketercapaian indikator dan nilai siswa yang lebih baik. Hasil penelitian ini menunjukkan bahwa penerapan Model Picture to Picturedapat meningkatkan keterampilan menulis teks deskripsi siswa kelas VIIA SMPN I Cipongkor Kabupaten Bandung Barat. Peningkatan tampak pada proses dan produk. Peningkatan proses terlihat pada aktivitas siswa dalam pembelajaran. Peningkatan tersebut terlihat dari kondisi siswa yang lebih fokus, lebih antusias, lebih mandiri, lebih aktif, dan senang dalam kegiatan pembelajaran. Peningkatan kualitas proses berdampak positif pada peningkatan kualitas produk. Hal tersebut terlihat pada hasil tes menulis deskripsi dari sikluss I hingga siklus II mengalami peningkatan.Nilai rata-rata kelas pada siklus I, yaitu sebesar 63 dan pada siklus II sebesar 83.Penulisan teks deskripsi dengan menggunakan model picture to picturememudahkan dan mengarahkan siswa dalam penemuan dan penuangan ide.Dapat disimpulkan bahwa model picture to picture dengan menggunakan media gambar-gambar tari daerah merupakan salah satu teknik yang mampu meningkatkan keterampilan menulis teks deskripsi siswa di SMPN 1 Cipongkor.